Một số biểu hiện của nhân sinh quan Phật giáo trong Truyền kỳ mạn lục của Nguyễn Dữ - Phạm, Văn Hóa (Đại học Đồng Tháp, 2023)
Buddhist culture has a great impact upon Vietnamese ancient culture. Vietnamese central literature is affected by Buddhist culture in the stages of development. This paper studied the ideas of karma, reincarnation and hell and their influence on the content and art form of truyen ky tales (strange/mythical tales) associated with Buddhist outlook on life in the Collection of Strange Tales (Nguyen Du). This article, on analyzing the manifestation of the Buddhist outlook on life in the Collection of Strange Tales, contributes to justifying the feeling of helpless resentment in the screams of Nguyen Du